RADIOLOGICAL HEALTH RISK ASSESSMENT AT ASHAKA CEMENT COMPANY, GOMBE STATE, NIGERIA - Abba, Habu Tela; Babakura, Abbas (FUDMA JOURNAL OF SCIENCES, 2020)
Enhanced natural radioactivity due human activities can be harmful to the environment and human health depending on the amount of exposure. A sensitive gamma spectrometry system consisting of 7.6cm x 7.6cm Nal(Tl) scintillation detector coupled with Canberra series 10 plus multichannel analyzer was used to determine the radioactivity concentration of natural radionuclides 232Th, 238U, and 40K in soil samples collected from the five communities around Ashaka Cement Company. The results obtained showed that the radionuclides are present in the soil samples in varying concentrations ranging from 11.36 Bq kg−1 measured in Badabdi to 98.06 Bq kg−1 in Ashaka Cement for 238U, from 13.21 Bq kg−1 in Jajami to 44.36 Bq kg−1 in Ashaka Cement for 232Th and from 65.50 Bq kg−1 in Gwangila to 415.62 Bq kg−1 in Julgwal Barkono for 40K. Absorb dose rate and annual effective dose rate due to these radionuclides are in the range 36 nGy h−1 in Badabdi to 50 nGy h−1 in Ashaka Cement and 0.132 mSv to 0.194 mSv in Badabdi and Ashaka Cement, respectively. These results are within global limits recommended by UNSCEAR. Therefore, the environmental matrices around the factory could be used without any restrictions